Determinan Perilaku Seks Pra Nikah Menurut Teori Health Belief Model: Studi Literatur Tahun 2021-2025 - Nabila Amelia Kirani; Luqman Effendi (Barongko: Jurnal Ilmu Kesehatan, 2026)
Premarital sexual behavior among adolescents in Indonesia shows a worrying trend. Negative impacts such as sexually transmitted infections (STIs), unwanted pregnancies, and even dropping out of school pose a serious threat to adolescents' futures. The Health Belief Model (HBM) theory is used to understand how individual beliefs influence preventive measures against these risky behaviors. This study aims to identify determinants of premarital sexual behavior among adolescents based on the six main components of the HBM through a literature review. This study used a literature review method of academic sources from Google Scholar and PubMed databases for the period 2021-2025. The analysis was conducted descriptively by grouping findings based on the variables of perceived susceptibility, perceived severity, perceived benefits, perceived barriers, cues to action, and self-efficacy. A literature review shows that perceived severity, perceived benefits, and self-efficacy consistently have significant relationships with efforts to prevent promiscuity. Meanwhile, perceived susceptibility and perceived barriers show varying results and are not always significant in every context. Health education interventions based on the Human Behavior Model (HBM) have been shown to be effective in increasing adolescent knowledge and self-efficacy. The HBM approach is a valid instrument for mapping the determinants of adolescent sexual behavior. Strengthening self-efficacy and personal internalization of risk are key to the success of health promotion programs.